Economic valuation of the bank of germoplasma of mango (mangifera indica) of the Universidad Nacional Hermilio Valdizan of Huánuco - Gonzáles Pariona, Fernando (2009)
The research work was conducted at the Fruit Orchard Olericola of the National University Hermilio Valdizán. The research was a descriptive and explanatory, exploratory to a level with a population of 14 varieties of plants in the Garden of Mango Fruit and Olerícola; assessed the different data set in the project, achieving production estimating the economic valuation of the Germplasm Bank. The results reveal that there are varieties with high productivity of fruits such as varieties Chulucanas (667 fruits per plant), with Julia and 525 fruits per plant Curazal 364 fruits per plant. We also found varieties with low productivity such as Kent and Tool Beat (35 and 68 fruits per plant, respectively) and another variety that was in Anera (Amine). We conclude that the economic potential of the fruit of the mango orchard of the Germplasm Bank of the Fruit UNHEVAL would be bordering on the S /. 77 265.15 nuevos soles per year.